Ответы и объяснения

2014-03-03T20:07:14+04:00
Лучший Ответ!
2014-03-03T20:11:56+04:00
35.a
x^4-13x^2+36=0
пусть t=x^2, тогда
t^2 - 13t +36 = 0
D=169-144=25
t1 = (13 - 5)/2 = 4                                     t2 = (13+5)/2 = 9
Обратная замена:
x^2 = 4                                                       x^2 = 9
x = 4, x = -4                                               x = 3, x = -3

35.b
-2x^6 + 9x^3 - 4 = 0
пусть t= x^3, тогда
-2t^2 + 9t - 4 = 0
2t^2 - 9t + 4 = 0
D = 81 - 4*2*4 = 49
t1 = (9+7)/4 = 4                                      t2 = (9-7)/4 = 1/2
Обратная замена:
x^3 = 4                                                                 x^3 = 1/2 
x = +-(корень третьей степени из 4)          x = +-(корень третьей степени из 2^-1)